Technical and economic calculation of a solar-powered charging station for electric vehicles - Hnatov, A.; Arhun, Shch.; Hnatova, H.; Sokhin, P.; Гнатов, А. В.; Аргун, Щ. В.; Гнатова, Г. А.; Сохін, П. А. (Харківський національний автомобільно-дорожній університет, 2021)
Development and implementation of green technologies is both an urgent and a cost-effective scientific and engineering task. Therefore, the issues related to the study of renewable energy sources, which are used as the main sources of energy for electric vehicles, are quite relevant and promising. At the same time, an equally important question is how profitable is building solar charging stations in terms of both ecology and economy. Goal. The aim is calculation and analysis of technical and economic indicators of a solar charging station for electric vehicles (EV). Methodology. The analytical methods of studying the development and application of the ways and devices to transform the energy of the sun into electricity are used, as well as the methods of experimental research and mathematical methods of processing and modulation of the received results; methods of calculating technical and economic indicators. Results. The review of the literature on the development of renewable energy sources, in particular, solar power plants, and the spread of electric vehicles with the gradual displacement (replacement) of traditional cars working on internal combustion engines with electric vehicles (BEV and PHEV) was made. The main parameters and technical characteristics of the solar-powered charging station (SPCS) were studied. For the analysis and calculation of technical and economic indicators of SPCS for EV it is offered to take a SPP with a capacity of 20 kW as a basis. The calculation of SPCS electricity generation both for own consumption and for power supply of EV and the sale of surplus electricity to the general network at the “green tariff” was carried out. Originality. The technical and economic calculation of SCS was made taking into account the rise of electricity prices in Kharkiv region (Ukraine). Practical value. According to the analysis of the obtained results, it can be said that the payback period of SPCS for EV is about 7.9 years. If we consider the constant increase in the cost of electricity (approximately 15% per year), we can expect the payback after 6.8 years of operation.
Техніко-економічний розрахунок сонячної зарядної станції для електромобілів
Keywords: solar-powered charging station; green energy; green tariff; solar energy; solar power plant; electric car; energy-efficient technologies; solar panels; сонячна зарядна електростанція; зелена енергетика; зелений тариф; сонячна енергетика; сонячна електростанція; електромобіль; енергоефективні технології; сонячні панелі; 621.311; 10.30977/AT.2019-8342.2021.49.0.05